Effect of start-up solvent on the performance of Co catalyst for Fischer-Tropsch synthesis in stirred-tank reactor. (15th July 2020) - Badoga, Sandeep; Gnanamani, Muthu Kumaran; Martinelli, Michela; Sparks, Dennis E.; Ma, Wenping
Graphical abstract: Highlights: Polar, non-polar starting solvents were tested for FTS on Co/Al2 O3 catalyst in CSTR. Non-polar solvent with high MW (Polywax3000) show higher catalyst deactivation rate. High polarity solvent (glycerol) adsorbs at catalyst surface thus low conversions. Olefin/Paraffin ratio was higher for polar solvents at similar conversions. Polar 1-Octanol and non-polar Polywax 655 has potential for best starting solvent. Abstract: The starting solvent is essential for carrying out Fischer-Tropsch (FT) synthesis in a stirred-tank reactor. The most commonly used solvents are C28+ hydrocarbon oils, wax, heavier wax, and FT wax. In general, FT activity of Co-based catalysts was found to decrease for initial days, and one of the reasons may be related to the filling of catalyst pores with heavier wax leading to lower gas diffusions and thus lower CO conversion. In this work, therefore, solvents with varying molecular weight and polarity, including glycerol, 1-octanol, Polywax-655, and dimethyl phthalate were tested as a starting medium for 0.27%Ag-25%Co/Al2 O3 catalyst. It was found that low molecular weight non-polar solvent, for example, Polywax 655 showed higher conversions. On the other hand, glycerol a high polar solvent tends to firmly bound with a catalyst surface and the associated water produced during FT synthesis could trigger catalyst deactivation from the oxidation of cobalt. This indicates the superiority of non-polar over polar solvents for FT synthesis. However, 1-octanol as a starting solvent showed the least catalytic deactivation rate and competitive FTS activity. Thus, 1-octanol has the potential as a start-up solvent for FT reaction in stirred tank reactors.